FROM FUN TO ADDICTION: HOW MICROTRANSACTIONS AND LOOT BOXES CONTRIBUTE TO GAMING DISORDER AND MENTAL HEALTH CHALLENGES IN FEMALE ADOLESCENTS - Yadav, Richa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The monetisation of gaming platforms has been researched over the period of time highlighting its limitations involving proper regulation. There are also investigations based on psychological effects that might generate interesting results. The study here attempted to investigate 600 female adolescent gamers from India who are actively a part of the online gaming world. These respondents belong to either government or private schools and colleges equally distributed over the sample. The investigation is undertaken using various statistical tools that help in identifying the perception of these gamers towards such microtransactions. The results showed that the female gamers have a lower level of engagement in real monetary transactions occurring in the virtual world. Majority of them are not involved in any kind of such transactions whereas the minimum of them agree to have bought a loot box. The perception towards such transactions among the gamers are found to be highly aware of the potential risk it might carry and always having a limitation to the spends on them. The gamers are found to be highly conscious of the financial consequences that can occur as a result of participating in such transactions and agree on adhering to them. There are no differences observed in the perception about microtransactions based on them att